2012
DOI: 10.1177/0890334412444005
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Neonatal Weight Loss in Healthy Term Infants

Abstract: Breastfeeding, compared to formula feeding, may not be a risk factor for greater early neonatal weight loss, at least in contexts in which weight is routinely monitored, breastfeeding is repeatedly assessed and appropriately supported, and careful supplementation is prescribed to limit and promptly treat excess weight loss and its related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 52 publications
3
54
3
1
Order By: Relevance
“…Özdeğirmenci et al investigated the efficacy of MPA, lineterol and NETA from oral progestins in simple atypical EH treatment. After 10 days of cyclic therapy, all three regimens had similar efficacy in treatment at the end of the third month [13]. In our study, the most commonly used oral progesterone agents in our gynecology clinic were linesterol and NETA, and most of the patients (93%) were found to have regression.…”
Section: Discussionsupporting
confidence: 57%
“…Özdeğirmenci et al investigated the efficacy of MPA, lineterol and NETA from oral progestins in simple atypical EH treatment. After 10 days of cyclic therapy, all three regimens had similar efficacy in treatment at the end of the third month [13]. In our study, the most commonly used oral progesterone agents in our gynecology clinic were linesterol and NETA, and most of the patients (93%) were found to have regression.…”
Section: Discussionsupporting
confidence: 57%
“…McDonald also reported the same results in this regard (6.6% versus 3.5%) (13). The results of the present study are consistent with the findings of most previous studies (13,15,20); however, Davanzo et al reported that the mean WL in infants, who were breastfed was lower than those fed with infant formula (6.3% versus 7.5%) (16). This is inconsistent with the results of the present study and the concept that is widely accepted by the experience and knowledge of health care staff.…”
Section: Discussionsupporting
confidence: 92%
“…If these measures are taken before childbirth, they could reduce NWL in infants. Another reason for NWL in infants fed with formula in the present study was the late start of feeding with formula after a period of deprivation of breast milk (16).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations